The Polemic of Child Custody Rights After DivorceBased On Islamic and Gender Justice Perspectives - Adibah, Syifa; Patul, Hali; Melisa; Erawati, Desi (Syams, 2025)
This paper aims to examine more deeply the polemics in child custody after divorce by reviewing Islamic perspectives and gender justice.This research uses a descriptive qualitative approach with a literature review method to analyze the polemics over childcare rights after divorce in the perspective of Islam and gender justice. This research shows that in the polemics over child custody after divorce, the main focus should not be on who is entitled to custody, but how the two parents, father and mother can work together in meeting the needs of love and welfare of the child. In the Islamic perspective, both father and mother have responsibilities towards children according to their respective roles. This research provides insight into how the concept of child custody in Islam can be applied fairly by considering the principles of gender justice and the best interests of the child. The results of this study can also be a reference for legal practitioners, policy makers, and parents in managing child custody in a more inclusive and child welfare-oriented manner.